A Systematic Review on Phytochemistry and Pharmacological Activity of the Plant Hymenocallis littoralis (Jacq.) Salisb - Talukdar, Saurav; Kumar, Suman; Bezbaruah, Sarbanga; Kashyap, Prerana; Ahmed, Mohsin; Majumder, Rupjyoti; Das, Rajsekhar; Singh, N. Anirudh (Pharmacognosy Reviews)
Hymenocallis littoralis (Jacq.) Salisb., commonly known as the Beach spider lily is a perennial herbaceous plant that belongs to the family Amaryllidaceae; well known for its distinctive ethnomedicinal uses against different serious ailments. The review critically analysed the distribution, traditional uses, phytoconstituents, and pharmacological activity of the plant H. littoralis. All the information described in this study was collected by using the electronic databases comprising PubMed and Google Scholar using the general search terms “Hymenocallis littoralis”, “traditional uses”, “phytochemical”, and “pharmacological activity”. The outcome of the study reveals that different parts of the plant, such as the bulb, root, stem, leaves, and flower, contain a wide variety of phytoconstituents, including alkaloids, flavonoids, phenolics, and volatile oils. To date, more than 30 alkaloids have been isolated from different parts of the plant. Among them, pancratistatin and lycorine are most commonly present, exhibiting diverse pharmacological activities. Similarly, other secondary metabolites such as phenolics and volatile oils are also isolated and reported in various scientific literature. The plant has also been reported for its significant traditional use by various indigenous communities in China, Mexico, Central America, and the Philippines for the management of wound healing, rheumatic joint pain, inflammation and pain, hemorrhoids, freckles, and blemishes. The pharmacological activity reveals that the plant shows potential anti-microbial, anthelmintic, anti-fungal, anti-cancer, anti-viral, and wound healing activity in various in vitro as well as in vivo. The study provides comprehensive and updated information regarding the plant profile and advocates the need for a clinical trial to find out unexplored lead molecules for drug discovery.
Keywords: Ethnomedicine; Hymenocallis littoralis; Pharmacology; Phytoconstituents.